Inflammasome Targeted Therapy in Pregnancy: New Insights From an Analysis of Real-World Data From the FAERS Database and a Systematic Review - Carnovale, Carla; Tombetti, Enrico; Battini, Vera; Mazhar, Faizan; Radice, Sonia; Nivuori, Mariangela; Negro, Enrica; Tamanini, Silvia; Brucato, Antonio (Frontiers in Pharmacology, 2021)
The published experience with biologics in childbearing age with autoimmune and inflammatory diseases mainly deals with the use of TNFα inhibitors (TNFα-i). Limited data are available for biologics targeting other cytokines or immunocompetent cells, especially for the inflammasome targeted therapy including IL-1 inhibitors and colchicine. We conducted a nested case-control study by using the US Food and Drug Administration Adverse Event Reporting System (FAERS) database aimed at quantifying the association between the use of IL-1 inhibitors/colchicine in pregnant women and the occurrence of maternal/foetal adverse effects. We used the reporting odds ratio (ROR) as a measure of disproportional reporting. From the total cohort (40 033 pregnant women), we retrieved 7 620 reports related to neonatal AEs, 2 889 to foetal disorders, 8 364 to abortion, 8 787 to congenital disorders, and 7 937 to labour/delivery complications. Inflammasome-targeted drugs did not present any disproportionate reporting for all these clusters of AEs. TNFα-i confirmed their safety during pregnancy with aROR <1 for all clusters of AEs except for labour complications. Finally, we performed a systematic review of the current literature. Data from the eligible studies (12 observational studies and 6 case reports; yielding a total of 2 075 patients) were reassuring. No major safety issues were reported and no trend could be identified in the reported malformations risk of inflammasome targeted therapies in pregnancy. However, due to limited data the routine use of these agents should only be considered in pregnancy if the benefit of maintaining disease control in the mother justifies any potential risk to the fetus.